Synthesis of 2-Amino-3-cyanopyridine Derivatives and Investigation of Their Antibacterial and Antifungal Properties - Mamedov, Ibrahim; Mamedov, Elshad; Gasimova, Irana; Mamedova, Yegana (Indonesian Journal of Chemical Research, 2023)
The aim of this study was to examine of antibacterial and antifungal activity of 2-amino-3-cyanopyridine derivatives against some microorganisms. The investigated compounds 2, 4, 6 exhibit promising antibacterial and antifungal activities. The high biological activities of the indicated compounds can be probably caused by the simultaneous presence of bromine atoms, nitro and amino groups in the molecules.